Disruptive prisoners: resistance, reform, and the New Deal - Clarkson, Christopher Allan (University of Toronto Press, 2021)
"Disruptive Prisoners reconstitutes the history of Canada's federal prison system in the mid-twentieth century through a process of collective biography - one involving prisoners, administrators, prison reformers, and politicians. This social history relies on extensive archival research and access to government documents, but more importantly, uses the penal press materials created by prisoners themselves and an interview with one of the founding penal press editors to provide a unique and unprecedented analysis. Disruptive Prisoners is grounded in the lived experiences of men who were incarcerated in federal penitentiaries in Canada and argues that they were not merely passive recipients of intervention. Evidence indicates that prisoners were active agents of change who advocated for and resisted the initiatives that were part of Canada's "New Deal in Corrections." While prisoners are silent in other criminological and historical texts, here they are central figures: the juxtaposition of their voices with the official administrative, parliamentary, and government records challenges the dominant tropes of progress and provides a more nuanced and complicated reframing of the post-Archambault Commission era. The use of an alternative evidential base, the commitment of the authors to integrating subaltern perspectives, and the first-hand accounts by prisoners of their experiences of incarceration makes this book a highly readable and engaging glimpse behind the bars of Canada's federal prisons."--